FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN PENERIMAAN PAJAK PENERANGAN JALAN Dl KOTA PALEMBANG - M Anwar Saddat; Didik Susetyo (Jurnal Ekonomi Pembangunan, 2004)
The purpose of this research is to analyze the effect of electric usage cost, income per capita and kWh of road lamp to the road lamp tax in Palembang. Theoritichal approach based on this research is Cobb-Douglas Functions. This research is supossed to be an information that explain the effect of electric usage cost, income per capita and kWh of road lamp. The data that is used in this research is secondary data  taken from many sources,  some of them are Badan  Pusat  Statistik,  Dinas  Pendapatan Daerah Palembang, PT PLN (Persero) district S2JB Palembang. The analysis of this research is by using the double linear regression model. The result shows that R Square value is 0,974. It mean that 97,4 persen of road lamp tax effected by electric usage cost, income per capita and kWh of road lamp. From t test can be concluded thaJ electric usage cost and kWh of road lamp are significant to road lamp tax, whereas income per capita is not significant because characteristic of tax that can be pressed Keywords: Road lamp tax, electric usage cost, income per capita and kWh of road lamp